Benthic macro-faunal abundance and diversity and sediment distribution in Akhziv submarine canyon and the adjacent slope (eastern Levant Basin, Mediterranean Sea) - RODITI-ELASAR, MIA; KEREM, DAN; LAZAR, MICHAEL; BARNEAH, ORIT; ALMOGI-LABIN, AHUVA; ANGEL, DROR L. (Mediterranean Marine Science, 2019)
The Israeli coastline is generally characterized by a broad and shallow continental shelf. Akhziv submarine canyon (ASC), in its northern reach, creates a locally unique marine ecosystem. The present study is the first to investigate the benthic macro-fauna of ASC, in order to assess its importance as a potential productivity ‘hotspot’ within its ultra-oligotrophic surroundings. Seven research cruises were conducted during 2010-2013, along ASC’s two channels and at iso-bathic control sites on the adjacent slope (AS), encompassing 8 sampling stations, at depths of 40-450 m. Bottom samples were collected by a Van Veen Grab, gravity corer and a GOMEX box corer. The infauna (≥500 µm) were counted and identified to the lowest possible taxonomic level. Sediments were analysed for grain size & composition and total organic carbon concentration. Mean benthic macro-faunal abundance (individuals/500ml ± SD) was higher inside the canyon (13.0±19.4) compared to the AS (2.9±3.3) (p=0.004), as was estimated true taxon richness (Chao1): 42.2 versus 10, respectively. Sediments’ mode grain size was found to be significantly higher in ASC’s eastern channel compared to AS (p=0.028), along with sand enrichment of up to 36%. The higher macrofaunal abundance and taxon richness may relate to a more heterogeneous sea bed provided by the higher diversity in grain size existing inside ASC. A relatively rich benthic realm, such as that observed in the ASC, may serve as a refuge for certain species and by hosting a relatively diverse assemblage, stands a better chance of adapting to changing conditions such as climate change.